1998
DOI: 10.1046/j.1365-2958.1998.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygenated mycolic acid composition on cell wall function and macrophage growth in Mycobacterium tuberculosis

Abstract: There are three major structural classes of mycolic acids in the cell envelope of Mycobacterium tuberculosis (MTB): alpha-, methoxy- and ketomycolate. The two oxygen-containing classes are biosynthetically related through a common alpha-methyl hydroxymycolate intermediate. BCG strains that fail to produce methoxymycolate and instead produce only keto- and alpha-mycolic acids show apparent defects in the O-methyltransferase MMAS-3. Overproduction of MMAS-3 from MTB resulted in a complete replacement of ketomyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 23 publications
(56 reference statements)
7
161
1
2
Order By: Relevance
“…To confirm this structure in more detail, we performed two-dimensional 1 H COSY NMR of the mmaA2 mutant ␣-mycolate. This study revealed that the vinyl protons are adjacent to protons at 2.02 ppm, consistent with previously reported resonances of vinyl protons in meromycolate chains (data not shown) (23). These findings are similar to our previous NMR findings when examining the ␣-mycolate of the pcaA mutant and establish that the mmaA2 mutant ␣-mycolate lacks either a proximal or distal cyclopropyl group.…”
Section: Construction Of An Mtb Mmaa2supporting
confidence: 92%
“…To confirm this structure in more detail, we performed two-dimensional 1 H COSY NMR of the mmaA2 mutant ␣-mycolate. This study revealed that the vinyl protons are adjacent to protons at 2.02 ppm, consistent with previously reported resonances of vinyl protons in meromycolate chains (data not shown) (23). These findings are similar to our previous NMR findings when examining the ␣-mycolate of the pcaA mutant and establish that the mmaA2 mutant ␣-mycolate lacks either a proximal or distal cyclopropyl group.…”
Section: Construction Of An Mtb Mmaa2supporting
confidence: 92%
“…MA cyclopropane ring is required for virulence and long-term persistence of pathogenic mycobacteria in mice 33,34 . Also, the relative differences in the amounts of keto-and methoxy-MA influence the intra-macrophage growth rate of M. tuberculosis 35 and the absence of keto-and methoxy-MA is associated with bacterial attenuation in mice 36 . The abundance of MA in M. tuberculosis cell wall appears to affect the course of tuberculosis in infected people.…”
Section: Mycolic Acidsmentioning
confidence: 99%
“…Whereas this diminishes the prospects of increasing the accuracy of mycolic acid antigen based immunodiagnostic tests for TB by using particular isomers of chemically synthetic mycolic acids, it eases the necessity for defining exactly the class composition of MA antigens that is used to detect the MA-binding antibodies. These MAs may resemble early stage M. tuberculosis when the keto-MA dominates or the late stage when the methoxy-MA dominates [131], with the only difference being slight changes in the magnitude of the signals for both MA antigen sets, with no difference in the ratio of the antibody binding signal from TB positive and TB negative patients.…”
Section: The Human Antibody Response To Mycolic Acidsmentioning
confidence: 99%